The Influence of Self-Regard on Response of Belief in God and Awareness of Prophetic Teaching - Mustafa Tekke; Nik Ahmad Hisham Ismail; Nooraini Othman; Sharifah Sariah Hassan (Intelektual Pustaka Media Utama, 2016)
Personality and religion relationship has long been studied by Western and Muslim researchers in order to find any association between religious factors anda person's behavior and thought. The present study sought to expand research by investigating the differences in the latent factors, namely Tawhid (Belief in God), Nubuwwa(Awareness of Prophetic Teaching), Self-striving, and Self-regard, in a newly developed scale of Integrative Islamic Personality Inventory (IIPI). The sample of this study was a group of undergraduate students (n= 1235) in ten universities in Turkey. Data were analyzed using Confirmatory Factor Analysis and Structural Equation Modeling. The main goal of this study was to investigate the statistical properties of this scale and examine if it could be applied across university students. It is apparent that Belief in God and Awareness of Prophetic Teaching, Self-regard and Self-striving represent psychological and social implications for individuals. Thus, the model of this research makes an important contribution to understanding and predicting how Muslims think, act, and experience Islam.